Longitudinal prognostic communication needs of adolescents and young adults with cancer. Issue 2 (30th September 2019) - Sisk, Bryan A.; Fasciano, Karen; Block, Susan D.; Mack, Jennifer W.
Abstract : Background: Although the majority of adolescent and young adult (AYA) patients with cancer desire prognostic information, to the authors' knowledge little is known regarding how preferences for prognostic communication change over time. Methods: The current study was a longitudinal, prospective, questionnaire‐based cohort study of 136 AYA patients with cancer who were aged 15 to 29 years and who were treated at a large academic cancer center. Previously published scales were administered at the time of diagnosis and at 4 months and 12 months after diagnosis. Results: The majority of patients reported that prognostic information was very/extremely important at the time of diagnosis (85%), at 4 months (96%; P = .002 compared with baseline), and at 12 months (81%; P = .02 compared with baseline). Few patients reported that prognostic knowledge was very/extremely upsetting at baseline (7%), at 4 months (9%; P = .44 compared with baseline), or at 12 months (11%; P = .27 compared with baseline). The majority of patients were satisfied with the amount of prognostic information received throughout the year after diagnosis (81%, 86%, and 81%, respectively, at the time of diagnosis, at 4 months, and at 12 months). This percentage did not change between the time of diagnosis and 4 months ( P = .16) or between diagnosis and 12 months ( P = 1.00). In multivariable analysis, satisfaction with prognostic information received was associated with patient report of high‐quality communication (odds ratio, 2.67; 95% CI, 1.38‐5.17) and having a >75% chance of cure (odds ratio, 2.39; 95% CI, 1.24‐4.61) after adjustment for patient age category, race/ethnicity, and time point of administration. Conclusions: The majority of AYA patients with cancer were satisfied with prognostic disclosure over time, but a sizeable minority wanted additional information. Desire for prognostic information increased over time. Clinicians should return to prognostic discussions over time to support AYA patients with cancer. Abstract : The majority of adolescent and young adult (AYA) patients with cancer are found to highly value prognostic information throughout the year after diagnosis. In the current study, although many AYA patients appear to be satisfied with the prognostic information received, a sizeable minority indicate unmet needs over time.